Nutritional anemias - Zeisel, Steven H.; Fussell, Susan; Cooksey, Karen; Lasswell, Anita; Kohlmeier, Martin ([Chapel Hill, N.C.] : Medeor Interactive Information, 2002)
Explores the biochemistry of vitamin B12, folate, and iron, and it describes food sources of these nutrients, and factors that enhance or impair absorption and bioavailability. Also identifies populations at risk and discusses the prevention, diagnosis, and treatment of nutritional anemias
Editor, Steven H. Zeisel
Narrator: Mike Urben
System requirements : Pentium CPU (200 MHz/32 MB RAM), windows 95/98/NT operating system or later, quad speed CD-ROM drive, sound card, monitor with screen resolution of 640 x 480, capable of running thousands of colors (16 bit), quick time 3.0 or highrer.
Keywords: Anemia -- Nutritional aspects; Nutrition disorders; Anemia